Rational and semi-rational engineering of cytochrome P450s for biotechnological applications - Lian-Hua Xu; Yi-Ling Du (Synthetic and Systems Biotechnology, 2018)
The cytochrome P450 enzymes are ubiquitous heme-thiolate proteins performing regioselective and stereoselective oxygenation reactions in cellular metabolism. Due to their broad substrate scope and catalytic versatility, P450 enzymes are also attractive candidates for many industrial and biopharmaceutical applications. For particular uses, enzyme properties of P450s can be further optimized through directed evolution, rational, and semi-rational engineering approaches, all of which introduce mutations within the P450 structures. In this review, we describe the recent applications of these P450 engineering approaches and highlight the key regions and residues that have been identified using such approaches. These “hotspots” lie within critical functional areas of the P450 structure, including the active site, the substrate access channel, and the redox partner interaction interface. Keywords: Cytochrome P450, Protein engineering, Rational design, Crystal structure